The Backside of Graphene: Manipulating Adsorption by Intercalation - Schumacher, Stefan; Wehling, Tim O; Lazić, Predrag; Runte, Sven; Förster, Daniel F; Busse, Carsten; Petrović, Marin; Kralj, Marko; Blügel, Stefan; Atodiresei, Nicolae; Caciuc, Vasile; Michely, Thomas (Nano letters, 2013)
The ease by which graphene is affected through contact with other materials is one of its unique features and defines an integral part of its potential for applications. Here, it will be demonstrated that intercalation, the insertion of atomic layers in between the backside of graphene and the supporting substrate, is an efficient tool to change its interaction with the environment on the frontside. By partial intercalation of graphene on Ir(111) with Eu or Cs we induce strongly n-doped graphene patches through the contact with these intercalants. They coexist with nonintercalated, slightly p-doped graphene patches. We employ these backside doping patterns to directly visualize doping induced binding energy differences of ionic adsorbates to graphene through low-temperature scanning tunneling microscopy. Density functional theory confirms these binding energy differences and shows that they are related to the graphene doping level.